Role of epigenetic in cancer biology, in hematologic malignancies and in anticancer therapy - Nwabo Kamdje, Armel Hervé; Dongmo Fogang, Hervet Paulain; Mimche, Patrice N. (Frontiers in Molecular Medicine, 2024)
Major epigenetic changes are associated with carcinogenesis, including aberrant DNA methylations and post-translational modifications of histone. Indeed evidence accumulated in recent years indicates that inactivating DNA hypermethylation preferentially targets the subset of polycomb group (PcG) genes that are regulators of developmental processes. Conversely, activating DNA hypomethylation targets oncogenic signaling pathway genes, but outcomes of both events lead in the overexpression of oncogenic signaling pathways that contribute to the stem-like state of cancer cells. On the basis of recent evidence from population-basedclinical and experimental studies, we hypothesize that factors associated with risk for developing a hematologic malignancy (HM), such as metabolic syndrome and chronic inflammation, may trigger epigenetic mechanisms to increase the transcriptional expression of oncogenes and activate oncogenic signaling pathways. Signaling pathways associated with such risk factors include but are not limited to pro-inflammatory nuclear factor κB (NF-κB) and mitogenic, growth, and survival Janus kinase (JAK) intracellular non-receptor tyrosine kinase-triggered pathways. The latter includes signaling pathways such as transducer and activator of transcription (STAT), Ras GTPases/ mitogen-activated protein kinases (MAPKs) /extracellular signal-related kinases (ERKs), phosphatidylinositol 3-kinase (PI3K)/Akt / mammalian target of rapamycin (mTOR), and βcatenin pathways. Recent findings on epigenetic mechanisms at work in the biology of cancer and in HMs and their importance in the etiology and pathogenesis of these diseases are herein summarized and discussed. Furthermore, the role of epigenetic processes in the determination of biological identity, the consequences for interindividual variability in disease clinical profile, and the potential of epigenetic drugs in HMs are also considered.